Perancangan Sistem Disinfektan UV-C Sterilisasi Paket sebagai Pencegahan Penyebaran Covid-19 - Reza Satria Rinaldi; Ika Novia Anggraini (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
This research is based on the societies' needs to sterilize the goods from delivery services during the Covid-19 pandemic. Due to the societies' needs, the delivery and logistics services did the sterilization of the goods by spraying disinfectant liquid in and out packages that gave impact to the wetness of packages. Therefore, innovation was needed to carry out the sterilization of goods and logistics so that they can be received or sent in good condition. The ultraviolet C (UV-C) disinfectant was this innovation. In this study, the design of a UV-C disinfectant system for sterilizing packages through a mini conveyor has been made. Then, a UV-C disinfectant system with a sterilization area of 90 cm long, 50 cm wide, and 50 cm high is used. The system needs a UV-C lamp with the power of 161.77 watts for the sterilization. The results of irradiation measurements of the UV-C disinfectant system is used to calculate the length of UV-C exposure time. Based on the calculation results, the designed UV-C disinfectant system was able to kill the virus up to 90% of the coronavirus within the length of UV-C exposure time toward the package in the sterilization area of at least 16 seconds.